2004
DOI: 10.1161/01.res.0000117307.57798.f5
|View full text |Cite
|
Sign up to set email alerts
|

Frequency- and Afterload-Dependent Cardiac Modulation In Vivo by Troponin I With Constitutively Active Protein Kinase A Phosphorylation Sites

Abstract: Abstract-Acute ␤-adrenergic stimulation enhances cardiac contractility, accelerates muscle relaxation, and amplifies the inotropic and lusitropic response to increased stimulation frequency. These effects are modulated by phosphorylation of calcium handling and myofilament proteins such as troponin I (TnI) by protein kinase A (PKA). To more directly delineate the role of TnI PKA phosphorylation, transgenic mice were generated that overexpress cardiac TnI in which the serine residues normally targeted by PKA ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
128
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 141 publications
(143 citation statements)
references
References 61 publications
14
128
0
1
Order By: Relevance
“…In IDAR, this TnI phosphorylation is thought to be responsible, at least for a significant part, for the faster relaxation. A likely role for TnI in frequencydependent processes is supported by the observations of Takimoto et al [7] and Bilchick et al [50]. These studies observed an effect of TnI phosphorylation via PKA as well as PKC that affected FFR and FDAR in intact murine hearts.…”
Section: Role Of Myofilaments In Fdarmentioning
confidence: 74%
See 1 more Smart Citation
“…In IDAR, this TnI phosphorylation is thought to be responsible, at least for a significant part, for the faster relaxation. A likely role for TnI in frequencydependent processes is supported by the observations of Takimoto et al [7] and Bilchick et al [50]. These studies observed an effect of TnI phosphorylation via PKA as well as PKC that affected FFR and FDAR in intact murine hearts.…”
Section: Role Of Myofilaments In Fdarmentioning
confidence: 74%
“…This important regulatory mechanism was first described in the year 1871; Henry Bowditch noted that the contractile force of the frog heart increased when it was paced at increasing frequency [1]. Since the first description of this force frequency relationship (FFR), the underlying mechanism has been a target for experimental investigation [2][3][4][5][6][7]. Although several contributing factors and modifiers of the FFR have been identified, our current understanding of frequency dependent activation is far from complete.…”
Section: Introductionmentioning
confidence: 99%
“…Yasuda et al [12] concluded from their studies of hearts of mice expressing these mutant forms of cTnI that phosphorylation of cTnI is a significant factor in cardiac relaxation with an importance similar to that of phospholamban phosphorylation. Takimoto et al [13] also reported that hearts of mice expressing cTnI-S23D/ S24D had a constitutive enhancement of rate-dependent increases in systolic and diastolic function in vivo. Along these lines, Varian and Janssen [14] reported a frequency dependent decrease in myofilament sensitivity to Ca 2+ associated with increasing heart rates and most likely attributable to cTnI phosphorylation.…”
Section: Specific Modifications In Troponin I Affect the Dynamics Andmentioning
confidence: 96%
“…The role of cTnI phosphorylation in the relaxant effect of adrenergic stimulation has also been emphasized in work reported by Stelzer et al [15] in studies of mice expressing cTnI-S23D/S24D against a cTnI and myosin binding protein C null background. These studies together with others provide compelling evidence for a prominent role of cTnI phosphorylation in the maintenance of power and frequency response in ejecting ventricles [13,[16][17][18][19]. Apart from their significant effects on cardiac dynamics, cTnI phosphorylation at the PKA sites affects length dependence of activation (LDA) [20].…”
Section: Specific Modifications In Troponin I Affect the Dynamics Andmentioning
confidence: 97%
See 1 more Smart Citation